Domestic Eucharists and Wedding Feasts in Fourth-Century Egypt: A Neglected Source from the Alexandrian Canonical Responses - Radle, Gabriel (Ex fonte, 2026)
While scholars have dedicated numerous studies to the gradual shifts in eucharistic practice of late antiquity – especially the move away from "sympotic eucharists" and the change from domestic spaces to purpose-built churches – one of the most important witnesses to the continued lay sponsorship of domestic eucharists is regularly ignored. The Canonical Responses, likely composed in fourth-century Egypt, contain a fascinating allusion to laity inviting clergy to offer the eucharist within the context of a domestic wedding feast. Unlike some of the late antique synodal and homiletic evidence for lay-sponsored eucharistic activities that tends toward criticism, the Canonical Responses give no condemnation of the practice as such. This article explores the potential context for such eucharists within the ritual landscape of weddings in late antiquity and underscores that while the relationship between eucharist and meal has never really disappeared from (esp. Eastern) Christian practice, the most significant eucharistic shift of late antiquity concerned precisely the link between family domestic feast and eucharist that the Canonical Responses still affirm as operative in fourth-century Egypt.